Silent partner : the graphic novel - Kellerman, Jonathan; Parks, Ande.; Gaydos, Michael (New York : Villard Books, 2012)
A graphic novel adaptation of the classic New York Times bestseller follows Alex Delaware, as he, driven by grief, tries to find the truth surrounding the death of an ex-lover, with the help of his trusted friend, homicide cop Milo Sturgis.
Keywords: Delaware, Alex -- (Fictitious character) -- Comic books, strips, etc; Kellerman, Jonathan. -- Adaptations; Child psychologists -- Comic books, strips, etc; Psychologists -- Comic books, strips, etc; Los Angeles (Calif.) -- Comic books, strips, etc; Graphic novels; Mystery fiction